Repurposing of antipsychotics perphenazine for the treatment of endometrial cancer. Issue 14 (15th July 2020) - Chen, Yang; Cui, Yunxia; Sun, Xiao; Wu, Huiwen; Ou, Manjiao; Tang, Yunzhe; Ni, Shuaishuai; Li, Xiaokang; Zhu, Jin; Mao, Fei; Wang, Yudong; Li, Jian
Graphical abstract: Abstract: Endometrial cancer (EC) is one of the most common and fatal gynecological cancers worldwide, but there is no effective treatment for the EC patients of progesterone resistance. Repurposing of existing drugs is a good strategy to discover new candidate drugs. In this text, perphenazine (PPZ), approved for psychosis therapy, was identified as a potential agent for the treatment of both progesterone sensitive and resistant endometrial cancer for the first time. Specifically, perphenazine exhibited good cell proliferation inhibition in Ishikawa (ISK) and KLE cell lines according to the CCK-8 assay and colony formation assay. It also reduced the cell migration of ISK and KLE cell lines in the light of the transwell migration assay. Annexin-V/PI double staining assay suggested that perphenazine could effectively induce ISK and KLE cell apoptosis. Moreover, results of western blot assay indicated perphenazine obviously inhibited the phosphorylation of Akt. Delightedly, PPZ also could significantly attenuate xenograft tumor growth at both 3 mg/kg and 15 mg/kg in mice without influencing the body weights.